JavaScript Bible, Fifth Edition - Morrison, Michael (Wiley Publishing, 2011)
This new edition of the definitive guide to JavaScript has been revamped to cover the latest browsers, language updates, extensions, and JavaScript standards Part tutorial and part reference, the book serves as a learning tool for building new JavaScript skills and a detailed reference for seasoned JavaScript developers Danny Goodman's exclusive interactive workbench, The Evaluator, makes it easy to master JavaScript and DOM concepts Offers deployment strategies that best suit the user's content goals and target audience